Penerapan Peraturan Daerah tentang Pelarangan Perilaku LGBT Ditinjau dari Mazhab Hukum Kodrat - Lahmuddin (LPPAIK Universitas Muhammadiyah Bandung, 2025)
Regional regulations prohibiting Lesbian, Gay, Bisexual, and Transgender (LGBT) behavior have become the focus of legal and humanitarian debates in various regions. This study aims to evaluate the implementation of regional regulations using a natural law approach. Basically, this approach refers to legal principles that are considered to originate from nature or the universe. This study uses a qualitative research method by conducting a literature review (library study), analyzing relevant legal sources and natural law philosophy, and tracing previous data and studies that examine the implementation of regulations on the prohibition of LGBT behavior. This study examines the legal aspects of the regional regulations and involves an analysis of the natural law perspective. There are ethical and human rights questions in assessing the validity of prohibitions on certain sexual identities and orientations. The natural law approach is the basis for evaluating whether the regulations are in accordance with natural principles and human values. This study considers the views of natural law experts, legal philosophy, and also religious views that underlie natural law. In this context, it is also possible to compare the natural law perspective with the dominant religious principles in the region.